Relations, Communication, Motivation and Rewards as Factors of a Successful Team and Organization (Journal of Universal Excellence, 2026)
Research Question (RQ): How to encourage employees and motivate them to remain part of a successful organization-team. What are the factors that influence the performance of the team?Purpose: The purpose of the research article is to show what is important for the successful operation of the teams and to show the system of a good team and team work. To examine the satisfaction and talent of employees for achieving success and to give a method that leads to a successful approach to managing people to a successful teamwork. Find out what are the factors that influence the success of a good team and company and whether good relationships, communication, motivation and rewarding for the success of a good team are important.Method: Various studies were used for the study, based on a substantive analysis of various articles from the existing literature of domestic authors. We used articles (from RUO and dLIB), graduate and master thesis. We have read articles, graduation thesis and master thesis and analyze them according to keywords.Results: The results of the survey show that the success of the organization depends on a successful group of people who work positively and are interlinked and share their knowledge and experience. Findings show that success requires communication, good relationships, motivation and rewarding.Organization: The research and study of various articles gives us information about the characteristics of the teams and the organizational culture of these, about the links between them and what impacts on success.Society: The employee is the one who brings the greatest success to the company, of course, if it is properly managed and directed.Originality: Most of the selected topics have focused on the growing awareness that education creates a broad range of skills that are crucial to development.Limitations/Future Research: We rely on research that has already been carried out in this field.
Keywords: team work; motivation; successful organization; team; talent of employees; success; rewarding; communication in the team